Guyana behavioural surveillance survey 2008/2009 and comparative analysis of 2003/2004 BSS and 2008/2009 BSS (National AIDS Programme Secretariat GeorgetownGY, 2010)
Presents report on the behavioural surveillance survey conducted by Guyana 2008/2009 and comparative analysis with 2003/2004.
Keywords: HIV